2019
DOI: 10.1007/s13337-019-00524-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide molecular evolution analysis of begomoviruses reveals unique diversification pattern in coat protein gene of Old World and New World viruses

Abstract: Begomoviruses (Family-Geminiviridae) are plant infecting single stranded DNA viruses known to evolve very fast. Here, we have analysed the DNA-A sequences of 302 begomoviruses reported as 'type isolates' from different countries following the list of International Committee on Taxonomy of Viruses till 2017. Phylogenetic analysis was performed which revealed two major evolutionarily distinct groups namely Old World (OW) and New World (NW) viruses. Our work present evidence that cp gene has varied degree of dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…The CPs of all the whitefly-transmitted geminiviruses have one or more antigenic epitopes in common, suggesting that these could be determinants of vector specificity and that they play a leading role in virus transmission [ 66 , 67 ]. Recently, an in silico study showed a higher mean diversity in the cp gene of OW BGVs compared to the NW [ 68 ]. However, highly mutable amino acids have been identified in the CP of Squash leaf curl China virus (SLCCNV) [ 69 ], which did not alter their fitness in the host plant but rendered the virus more competitive for certain species of whiteflies.…”
Section: Introductionmentioning
confidence: 99%
“…The CPs of all the whitefly-transmitted geminiviruses have one or more antigenic epitopes in common, suggesting that these could be determinants of vector specificity and that they play a leading role in virus transmission [ 66 , 67 ]. Recently, an in silico study showed a higher mean diversity in the cp gene of OW BGVs compared to the NW [ 68 ]. However, highly mutable amino acids have been identified in the CP of Squash leaf curl China virus (SLCCNV) [ 69 ], which did not alter their fitness in the host plant but rendered the virus more competitive for certain species of whiteflies.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably why this phenomenon is more in the CP region with the lowest mean dN/dS values, indicating that it is undergoing a stronger purifying selection. Other studies have also indicated similar patterns within begomoviruses, with the CP gene having the strongest evolutionary constraint [ 66 – 68 ]. dN/dS ratios are estimators of evolutionary bottlenecks imposed on a coding region at intra-specific levels.…”
Section: Discussionmentioning
confidence: 63%
“…This is probably why this phenomenon is more in the CP region with the lowest mean dN/dS values, indicating that it is undergoing a stronger purifying selection. Other studies have also indicated similar patterns within begomoviruses, with the CP gene having the strongest evolutionary constraint [66][67][68]. dN/dS ratios are estimators of evolutionary bottlenecks imposed on a coding region at intra-speci c levels.…”
Section: Discussionmentioning
confidence: 67%